DISEKSI ARTERI KAROTIS INTERNAL POSTPARTUM - Jimmy,* Ashari Bahar,* Andi Kurnia Bintang,* Muhammad Iqbal Basri* (NEURONA, 2018)
CAROTID ARTERY DISSECTION IS THE MOST COMMON CERVICOCEPHALIC ARTERY DISSECTION POSTPARTUM CERVICOCEPHALIC ARTERY DISSECTION IS A RARE CAUSE OF STROKE IN YOUNG ADULTS WE REPORT THE CASE OF A 27YEAROLD FEMALE PRESENTED TO THE EMERGENCY DEPARTMENT WITH LEFT HEMIPLEGIA OCCURRED SUDDENLY 4 DAYS PRIOR TO ADMISSION WHEN SHE WAS BREASTFEEDING HER5MONTHOLD BABY IN THE AFTERNOON PRECEDED BY A RIGHT HEADACHE